The experience of sepsis and the health-related quality of life (Research, Society and Development, 2019)
Sepsis is an infectious complication of high severity, with potential for evolution to death, both during hospitalization and after discharge. In survivors, are observed, losses in physical and cognitive aspects that affect Health-Related Quality of Life. The objective of this joint design study was to evaluate the Health-Related Quality of Life to sepsis survivors after hospital discharge, through the Medical Outcomes Study 36 – Item Short-Form Health Survey (Version two) and analyze their unique experiences through interviews to broaden the understanding of the multidisciplinary health team. Participated four individuals, and observed median and low Health-Related Quality of Life, whose analysis of qualitative data, according to the framework of psychoanalysis, was notably the polarization of the aspects of the body and illness.